Manajemen Pengembangan Karakter : Peran Orang Tua Dalam Mengatur Penggunaan Gadget Dan Dampaknya Bagi Ketrampilan Sosial Anak Pendidikan Dasar (Studi kasus siswa TK-SD di Kecamatan Blora) - Kristiyuana (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2024)
Character Development Management is crucial to implement, as the issue of character education and its management in Indonesia has yet to be fully integrated into the education system. The mids rapid technological, elementary school childrens are increasingly exposed to gadgets, which have the potential to affect how they interact with others. This study uses both qualitative methods, including surveys of parents and observations of children's behavior in social situations. The results show that parents who actively regulate their children's gadget usage tend to have children with better social skills. In contrast, children who have unlimited access to gadgets and receive less supervision from their parents tend to struggle with building social relationships, which can negatively impact their emotional development and interpersonal skills. This study aims to explore how parents can manage gadget use within the family, as well as understand its impact on the development of children's social skills. Additionally, the research discusses strategies that parents can apply to create an environment that supports character and social skills development, even in a technology-driven world. The findings of this study are expected to provide valuable insights for parents, educators, and policymakers in efforts to create a smart, balanced, and socially generation. Keyword: Character Development Management, Parental Role, Gadget Use, Social Skills, Elementary School Children